Wind resource assessment and siting for the expansion of Fakken wind park - Bjugg, Martine (UiT The Arctic University of Norway, 2023)
Norway is anticipated to experience an energy deficit in the coming years, and one solution to address this issue is the implementation of new renewable energy sources. To mitigate the projected energy deficit, increased energy production is required. With its considerable wind potential, the country offers ample opportunities for wind energy development. Consequently, there is a growing demand for accurate methods to identify suitable areas for establishing new wind farms. The study examines the wind conditions at Vannøya in Northern Norway and evaluates the performance of WRF and WAsP models in accurately estimating wind conditions and energy production at the existing Fakken 1 wind park. The study found that the WRF model's resolution was insufficient to capture terrain features that influence the wind conditions, and the model tended to underestimate the high wind speeds. Initially, the WRF model provided the closest estimation to the observed production at Fakken 1, with a 9% deviation on average. However, when considering the production losses that the models cannot capture, the WAsP model provided more accurate production estimates and better captured the variations in production within the wind park. For the proposed expansion, Fakken 2, the WAsP models estimated a yearly production of 173 GWh, while the WRF model estimated a production of 155 GWh. Additionally, the study proposed improvements in turbine positions for Fakken 2, with the potential for increased production. The WAsP model features and computational speed made it more suitable for wind resource assessment. LiDAR proved valuable in preliminary evaluations but unreliable as a sole measurement tool. Overall, the WAsP model was deemed more reliable and efficient for wind resource assessment and siting for the Fakken wind power plant.